2019
DOI: 10.1186/s13012-019-0953-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the implementation of the PACE Steps to Success Programme in long-term care facilities in seven countries according to the RE-AIM framework

Abstract: BackgroundThe PACE ‘Steps to Success’ programme is a complex educational and development intervention for staff to improve palliative care in long-term care facilities (LTCFs). In a cluster randomized controlled trial, this programme has been implemented in 37 LTCFs in 7 European countries. Alongside an effectiveness study, a process evaluation study was conducted. This paper reports on the results of this process evaluation, of which the aim was to provide a more detailed understanding of the implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…The present review suggested considerable variability in educational interventions and noted a lack of globally standardised interventions to date. Only one study attempted an intervention across seven countries; the findings showed great variances across and within these countries (Oosterveld‐Vlug et al, 2019; Van den Block et al, 2019). Implementation of their intervention was influenced by the programme itself and its delivery, how and what kind of people were involved in the programme and the implementing practice's context (Oosterveld‐Vlug et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present review suggested considerable variability in educational interventions and noted a lack of globally standardised interventions to date. Only one study attempted an intervention across seven countries; the findings showed great variances across and within these countries (Oosterveld‐Vlug et al, 2019; Van den Block et al, 2019). Implementation of their intervention was influenced by the programme itself and its delivery, how and what kind of people were involved in the programme and the implementing practice's context (Oosterveld‐Vlug et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study attempted an intervention across seven countries; the findings showed great variances across and within these countries (Oosterveld‐Vlug et al, 2019; Van den Block et al, 2019). Implementation of their intervention was influenced by the programme itself and its delivery, how and what kind of people were involved in the programme and the implementing practice's context (Oosterveld‐Vlug et al, 2019). Given that level of palliative care development and LTCFs differ from one country to another (Centeno et al, 2007; Clark et al, 2020; Froggatt et al, 2017) and that diverse educational backgrounds and practice experience of staff members, this study highlighted that preparing and providing standardised programmes that meet unique educational goals and needs has remained a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as was clear from the primary trial analyses, [5] the stepwise training of nursing home staff over a one-year period was not su cient to improve comfort in the nal days of life, which might be related to the intervention itself, the quality of its implementation in several nursing homes, a possible mismatch between the intervention and the primary outcome, or a combination of these factors. [5,23] Regarding the secondary outcome, the PACE program appeared to improve quality of care and dying in the last month of life equally for those with dementia (regardless of the stage) and those without dementia. Although these ndings need to be interpreted cautiously as this is a secondary outcome, they are remarkable, as this palliative care program only had a limited number of dementia-speci c elements as part of the training.…”
Section: Discussionmentioning
confidence: 99%
“…In light of care improvement in the field of palliative care in a nursing home context, recently a largescale research project, 'PACE steps to success', has been implementing a combination of tailored improvement initiatives focusing on communication, advance care planning and knowledge and skills on end of life care using a train-the-trainer implementation model. Although the intervention did not show significant effect on their primary outcome (comfort in the last week of life for residents), the process evaluation showed that the implementation rate was highly variable between countries and teams, and several challenges arose such as attitude and motivation of staff, and skills and expertise of the trainer appointed to the individual nursing homes (27,47). Our previous implementation research in palliative care already showed that caregivers are willing to invest in quality improvement trajectories and learning from other teams but they need support from their management and financial reimbursement or staff to engage in these activities (39).…”
Section: Responder Characteristicsmentioning
confidence: 91%
“…However, they mainly focus on the hospital or home setting or circumstances surrounding death such as symptoms and place of death (17)(18)(19)(20)(21)(22)(23)(24)(25). Although initiatives have been taken to improve palliative care in nursing homes (26)(27)(28), researchers were not yet able to validate and implement solid quality indicators for palliative care in this specific setting.…”
Section: Introductionmentioning
confidence: 99%